Plant-soil feedback in herbaceous species of Mediterranean coastal dunes - Bonanomi, Giuliano; Esposito, Assunta; Mazzoleni, Stefano (Biological Letters, 2013)
Plants induce soil heterogeneity that can affect species coexistence. In this work, the soil heterogeneity induced by the growth of 9 species selected from Mediterranean vegetation of coastal dunes was studied in controlled conditions. We investigated the effect of the grown plants on soil characteristics (pH, electrical conductivity, NO3 -, and NH4 +) and performance of 4 target species (Dactylis hispanica, Melilotus neapolitana, Petrorhagia velutina, and Phleum subulatum). Plant growth and survival were affected by soil history in species-specific ways, showing a high variability of both parameters, with survival ranging from 100% to 0%. Soil history did not affect soil pH and conductivity but dramatically changed the availability of mineral nitrogen forms. However, for all plant species, growth and survival results were unrelated to the measured soil characters. Other factors, such as accumulation of allelopathic compounds and/or changes in soil microbial communities, may explain the observed effects. The experimental results, demonstrating a widespread occurrence of plant-soil feedback, show the importance of this process also in species-rich herbaceous Mediterranean vegetation.